2019
DOI: 10.1097/sla.0000000000002583
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Postoperative Pain and Overall 30-Day Complications in a Broad Surgical Population

Abstract: Higher actual postoperative pain scores and unacceptable pain, even on the first postoperative day, are associated with more postoperative complications. Our findings provide important support for the centrality of personalized analgesia in modern perioperative care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
85
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(107 citation statements)
references
References 56 publications
4
85
0
4
Order By: Relevance
“…A previous study reported that poorly controlled postoperative pain is associated with increased morbidity, development of persistent pain, and prolonged opioid use. 27 Considering that severe postoperative pain is closely related to overall 30-day complications after surgery, 28 severe postoperative pain associated with inadequate analgesia could have affected the increase in 30-day unplanned readmission rate in this study as a confounder. However, in the matched cohorts, there was no significant difference between the proportion of pain as a chief complaint in 30-day unplanned readmissions in the neostigmine group (3.6%, 40/1124) and that in the sugammadex group (3.4%, 12/355) (P¼0.271).…”
Section: Chief Complaint For 30-day Unplanned Readmissionmentioning
confidence: 86%
“…A previous study reported that poorly controlled postoperative pain is associated with increased morbidity, development of persistent pain, and prolonged opioid use. 27 Considering that severe postoperative pain is closely related to overall 30-day complications after surgery, 28 severe postoperative pain associated with inadequate analgesia could have affected the increase in 30-day unplanned readmission rate in this study as a confounder. However, in the matched cohorts, there was no significant difference between the proportion of pain as a chief complaint in 30-day unplanned readmissions in the neostigmine group (3.6%, 40/1124) and that in the sugammadex group (3.4%, 12/355) (P¼0.271).…”
Section: Chief Complaint For 30-day Unplanned Readmissionmentioning
confidence: 86%
“…Secondly, our follow-up is limited to 48 hours and we did not evaluate postoperative complications. Nevertheless, our focus is to deeply understand the psychological vulnerability influence on postoperative pain, considering that adequate pain management is intrinsically linked to rehabilitation [32] and the reduction of complications [33]. Lastly, in a clinical study, it is not possible to directly assess and isolate the effect of each potential confounding factor of the dependent variables, especially because the number of predictors is high for such complex pain-related outcomes.…”
Section: Discussionmentioning
confidence: 99%
“… 3 , 7 This is surprising because evidence-based guidelines for the treatment of acute postoperative pain are generated continuously. 1 , 5 , 21 In addition, severe (and long-lasting) acute pain early after surgery is one major predictor for postoperative complications 26 and chronic postoperative pain. 6 One reason for the gap between available knowledge and insufficient therapy might be the different responses to pain and analgesics between individual patients.…”
Section: Introductionmentioning
confidence: 99%